Spanish Social Cinema: Analysis of Evolution and Implications for Social and Behavioral Sciences - Antonio Jesus Molina-Fernández; María Gemma Valero-Arroyo; Río Vázquez-Gomis; Florentino Moreno Martin (Social Sciences)
Social cinema is a cinematographic expression used to denounce current and historical problems, as well as to identify social limits and promote the transformation of society itself. To this end, works included in social cinema depict aspects of reality to critically influence it. The objective of this study is to examine the evolution of social cinema, as well as its scientific, economic and political bases and its main consequences for the general population. Method: This study was conducted by the application of the technique of qualitative research thematic analysis as a procedure in the process of the execution of the scientific task, related to a historical trend study of the research object. The search was carried out in the databases of IMDB and the Culture Ministry of Spain. The end of the dictatorship and the beginning of democracy (1975) was placed as the historical cutting point in the analysis. Various psychosocial variables were used as categories of analysis, including poverty, work, substance use, crime, urban and rural contexts, violence, etc. Results: Spanish social cinema has evolved since its origins in the 1950s as a reflection of Spanish society. These developments, including both progressions and regressions, have been connected with social, political and economic factors. Conclusions: While the shape of Spanish social cinema has changed over time, its themes have remained similar since the origin: poverty, work and hopelessness. The evolution has not been continuous, as it has fluctuated in response to the claims and requests from the context. The Spanish social cinema has reflected topics and images from Spanish society, even when the sociopolitical context avoided them. Finally, the legitimacy of Spanish social cinema is based on its cultural strength and social/political commitment.